UMSU FM'S Communication Strategy on the Talk Show Prevent HIV Ending Aids To Develop Existence In the Digital Era - Alfina, Sherly; Winda Kustiawan (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
ABSTRACT In the current digital era, how can Radio 91.6 UMSU FM's communication strategy in its talk show content ''Prevent HIV, End AIDS'' be optimized to expand its audience reach and maintain its relevance amidst increasingly fierce media competition? This research was conducted using a qualitative descriptive method. This research was conducted on Radio 91.6 Umsu FM, by looking for valid data and information about how Umsu radio is developing its existence in the current digital era with one of its programs, namely the Prevent HIV End AIDS Talkshow. This program was presented by the North Sumatra KPA for outreach via radio and also includes a program that educates the public so that they have awareness of handling HIV AIDS, therefore it has become a weekly broadcast on radio specifically for the community, teenagers, and HIV AIDS sufferers. Indeed, technological advances should be used as a means for the development of media so that it is not left behind by other competitors. The results of the effects on communication strategies include cognitive effects, affective effects, and conative effects that make information heard more and more. Keywords: Media Strategy, Existence, Radio 91.6 UMSU FM.